2021
DOI: 10.52312/jdrs.2021.225
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of free gracilis muscle transfer for the restoration of elbow flexion in traumatic brachial plexus palsy

Abstract: Traumatic brachial plexus palsy (TBPP) is a devastating injury that significantly affects the upper extremity functions and results in serious disability. Surgical reconstruction is closely related to the severity of the injury and the time elapsed after the trauma. Microneural and/or free functional muscle transfer reconstruction can be performed in patients admitted in the early period. [1][2][3] Tendon transfers, pedicle or free muscle transfers are the treatment options in patients with delayed TBPP and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Maldonado et al [ 21 ] concluded that distal attachment to the FDP/FPL achieves better elbow flexion strength and ROM than attachment to the biceps tendon. Although no studies, to our knowledge, have compared the effect of distal insertion on motor outcomes, other small case series have described some alternatives to distal attachment to the biceps, forearm extensor, or flexor tendons [ 3 , 17 ]. So far, the best results were achieved by Doi et al [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maldonado et al [ 21 ] concluded that distal attachment to the FDP/FPL achieves better elbow flexion strength and ROM than attachment to the biceps tendon. Although no studies, to our knowledge, have compared the effect of distal insertion on motor outcomes, other small case series have described some alternatives to distal attachment to the biceps, forearm extensor, or flexor tendons [ 3 , 17 ]. So far, the best results were achieved by Doi et al [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first one is strongly adhered to the time factor, 7 the second one, which is aimed to restore independent EF, is not affected by the latter. 5 6 Since functional free muscle transfers 8 remain the prerogative of highly specialized microsurgical centers with a long history of successful utilization of the technique with low morbidity rate of the transferred myocutaneous flap, 9 approaches to the reconstruction of an effective EF remain dependent on the two abovementioned “classical” techniques, 3 4 5 6 available to most surgeons.…”
Section: Introductionmentioning
confidence: 99%